Co-inoculation of Rhizobium tropici and Azospirillum brasilense in common beans grown under two irrigation depths - Peres, Amanda Ribeiro; Ferreira Rodrigues, Ricardo Antonio; Arf, Orivaldo; Portugal, José Roberto; Dias Chaves Corsini, Daiene Camila (Revista Ceres, 2016)
The alternative technique of co-inoculation or mixed inoculation with symbiotic and non-symbiotic bacteria has been studied in leguminous plants. However, there are few field studies with common beans and under the influence of the amount of irrigated water. Thus, the objective of this study was to evaluate the efficiency of inoculation and coinoculation of common beans with Rhizobium tropici and Azospirillum brasilense under two irrigation depths. The experiment was carried out in the winter of 2012 and 2013, in Selvíria, state of Mato Grosso do Sul. The experimental design was composed of randomized blocks in split-plot scheme with two irrigation depths in the plots (recommended for common beans and 75% of the recommended) and five forms of nitrogen (N) supply in the split-plots (control noninoculated with 40 kg ha- 1 of N in topdressing, 80 kg ha- 1 of N in topdressing, A. brasilense inoculation with 40 kg ha- 1 of N in topdressing, R. tropici inoculation with 40 kg ha-1 of N in topdressing, and co-inoculation of A. brasilense and R. tropici with 40 kg ha- 1 of N in topdressing) with four repetitions. Co-inoculation increased nodulation in the second year of cultivation. None of the evaluated treatments increased the grain yield in relation to non-inoculated control with 40 kg ha-1 of nitrogen in topdressing, which presented average yield of 2,200 kg ha-1. The use of 75% of the recommended irrigation depth provides similar grain yield to the recommended irrigation depth in common beans cropped in winter.